Effect of castration time on feedlot performance, carcass characteristics, and beef tenderness - Homm, J.W.; Marston, T.T.; Brethour, J.R.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred Angus calves (n=120) were randomly assigned to early-castrated, early-castrated plus implant, and late-castrated treatment groups. After weaning, calves were placed on feed at the Western Kansas Agricultural Research Station in Hays, Kansas, for finishing. On-feed weights and final weights were similar among treatments. During the first 132 days on feed, the steers castrated early and implanted had a lower average daily gain than early- and late-castration treatments. Early castrates tended (P=0.08) to have a lower feed-to-gain ratio for the first 132 days on feed. Hot carcass weight, internal fat, and marbling scores were not affected by treatment. Carcasses from steers castrated late had less backfat, larger ribeye areas, and lesser yield grades (greater cutability) than carcasses from steers castrated early, with or without an implant. Carcasses from steers castrated early and implanted had a greater percentage grading USDA choice (60%) than did carcasses from steers castrated early (45%) or late (41%). Warner-Bratzler shear force and sensory-panel traits were similar for all treatment groups.
Keywords: Beef; Castration; Feedlot performance; Carcass characteristics; Beef tenderness